Du statut d’un cadre conceptuel dans une recherche qualitative - Ethier, Marc-André (Recherches qualitatives, 2003)
Qualitative research has often been criticized for its methodological slip towards positivism and especially for its neglect of the dynamic relation between the themes it develops. This article aims at suggesting a qualitative method capable of addressing these difficulties. The authors suggest that Plan Analysis (Caspar, 1995, 1997) is a valid and feasible method to highlight the dynamic links between the themes that emerge using traditional theme analysis. The use of Plan Analysis is illustrated using a study on the motivation for treatment in pedophile sex abusers.